Determining effect of seagrass-mediated CO2 flux on the atmospheric cooling potential of a subtropical intertidal seagrass meadow. (March 2023) - Zheng, Pengxiang; Chen, Guangcheng; Lan, Wenlu; Li, Shiman; Li, Mingmin; Chen, Shunyang; An, Wenshuo; Chen, Jiahui; Yu, Shuo; Chen, Bin
Abstract: Atmospheric greenhouse gas (GHG) emissions from seagrass meadows that determine the ecosystem atmospheric cooling effect have rarely been quantified. This study measured the simultaneous fluxes direct to the atmosphere of three GHGs (CO2, CH4 and N2 O) within a Halophila beccarii seagrass meadow and an adjacent unvegetated bare intertidal flat, and their relationships to seagrass abundance and relevant soil parameters. The results showed that seasonal variation in seagrass abundance was strongly linked with the CO2 exchange rate. The CH4 and N2 O fluxes were similarly low at both sites and comparable between winter and summer. The global warming potential of CH4 and N2 O reduced the ecosystem CO2 uptake by only 5 % at the seagrass site. The results indicated that the H. beccarii meadow had a stronger atmospheric cooling effect than the bare flat and that the seagrass-mediated CO2 flux in this oligotrophic seagrass meadow primarily determined the atmospheric cooling effect. Graphical abstract: Unlabelled Image Highlights: Flux of three GHGs is measured within a intertidal seagrass meadow and adjacent flat. Seasonal variation in plant abundance is closely linked with the CO2 exchange rate. Seagrass-mediated CO2 flux mainly determines the ecosystem atmospheric cooling effect. H4 and N2 O fluxes are low without significantly seasonal or spatial variation. Seagrass meadow loss to bare flat will increase climatic forcing.